Ultrastructural Changes ·In Ram Sperm Head During ln-viitro _Acrosome Reaction - AHMED, K (The Indian Journal of Animal Reproduction, 2023)
Ram Spermatozoa were incubated for 6 hrs in Hepes diluent at 39°C. The ultrastructuralchanges of sperm head during acrosome reaction were studied using electron microscope. Fusionof outer acrosomal membrane with plasma membrane forming a vesicle were observed in 58.17±0.79, 70.33±1.07 and 71.0±0.94 percent spermatozoa containing 100 x 106 , 250 x 106 and 500 x 106sperm per ml Hepes diluentrespectively. The non specific degeneration and absence of acrosome was 31 .67±0.04 and8.33±0.61 in 100 x 106 sperm / ml,19.5±0.46 and 6.67±0.84 in 250 x 106sperm / ml and 17.0±0.88 and 8.67±1.05 in 500 x 106 sperm / ml respectively.
Keywords: ln-viitro _Acrosome reaction